Early Initiation of a Standardized Open Abdomen Treatment With Vacuum Assisted Mesh-Mediated Fascial Traction Achieves Best Results - Berrevoet, Frederik; Lampaert, Silvio; Singh, Kashika; Jakipbayeva, Kamilya; van Cleven, Stijn; Vanlander, Aude (Frontiers in Surgery, 2021)
Background: The open abdomen (OA) is an important approach for managing intra-abdominal catastrophes and continues to be the standard of care. Complete fascial closure is an essential treatment objective and can be achieved by the use of different dynamic closure techniques. Both surgical technique and—decision making are essential for optimal patient outcome in terms of fascial closure. The aim of this study was to analyse patients' outcome after the use of mesh-mediated fascial traction (MMFT) associated with negative pressure wound therapy (NPWT) and identify important factors that negatively influenced final fascial closure. Methods: A single center ambispective analysis was performed including all patients treated for an open abdomen in a tertiary referral center from 3/2011 till 2/2020. All patients with a minimum survival >24 h after initiation of treatment were analyzed. The data concerning patient management was collected and entered into the Open Abdomen Route of the European Hernia Society (EHS). Patient basic characteristics considering OA indication, primary fascial closure, as well as important features in surgical technique including time after index procedure to start mesh mediated fascial traction, surgical closure techniques and patients' long-term outcomes were analyzed. Results: Data were obtained from 152 patients who underwent open abdomen therapy (OAT) in a single center study. Indications for OAT as per-protocol analysis were sepsis (33.3%), abdominal compartment syndrome (31.6%), followed by peritonitis (24.2%), abdominal trauma (8.3%) and burst abdomen (2.4%). Overall fascial closure rate was 80% as in the per-protocol analysis. When patients that started OA management with MMFT and NPWT from the initial surgery a significantly better fascial closure rate was achieved compared to patients that started 3 or more days later (p < 0.001). An incisional hernia developed in 35.8% of patients alive with a median follow-up of 49 months (range 6–96 months). Conclusion: Our main findings emphasize the importance of a standardized treatment plan, initiated early on during management of the OA. The use of vacuum assisted closure in combination with MMFT showed high rates of fascial closure. Absence of initial intraperitoneal NPWT as well as delayed start of MMFT were risk factors for non-fascial closure. Initiation of OA with VACM should not be unnecessary delayed.